MENUMBUHKAN SEMANGAT BELAJAR SISWA SEKOLAH DASAR DALAM PROSES PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 MELALUI INTERVENSI BIMBINGAN DAN KONSELING - Muhammad Taufiq Firdaus; N Nurjannah (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2021)
Various surveys and studies show that the online learning process makes some students experience a decreased enthusiasm for learning. To foster students' enthusiasm for learning, of course it is influenced by many things, one of which is through counseling guidance services. So, this study aims to see how counseling guidance efforts to foster the enthusiasm of primary school students' learning in the online learning process during the COVID-19 pandemic. The research method uses a qualitative approach with the type of case study, the research subject is the party providing counseling guidance services at SD Martadah Baru, object of this research is how the counseling guidance models and techniques are used in an effort to foster learning enthusiasm for primary school students. The results of this study indicate that in an effort to foster students' enthusiasm for learning, counselors use a behavior counseling model with modeling and storytelling techniques. Then also carry out education or some kind of providing understanding to parents of students, related to their very important role in the online learning process, such as accompanying, supervising, supporting and facilitating children when learning activities from home. Behaviorism is a theory to shape behavior, which can be used to achieve certain goals or targets, such as growing students' enthusiasm and motivation to learn. Modeling techniques can change students' behavior, attitudes and characteristics into enthusiasm for learning because they are motivated by their role models. Storytelling techniques can be used to foster students' enthusiasm for learning, because it is in accordance with their character who was in a fantasy period.